Metallographic and Magnetic Properties of Antarctic Meteorites: Allan Hills A77255, Derrick Peak A78003 and A78007, and Russian Meteorite Sikhote-Alin - Fisher, R.M.; Szirmae, A.; Nagata, Takesi (1980)
P(論文) The metallographic and magnetic properties of three iron meteorites from Victoria Land in Antarctica have been studied along with similar analyses of the Russian meteorite Sikhote-Alin. Allan Hills A77255 contains 12.2% Ni, 0.61% Co, and 0.026% P, and consists of a fine intergrowth of kamacite spindles in a microplessitic matrix. Derrick Peak A78003 contains 5.4% Ni, 0.51% Co, and 0.40% P, and was heavily deformed during entry through the earth's atmosphere. Derrick Peak A78007 contains 7.3% Ni, 0.38% Co, and 0.75% P. Extensive shear deformation of schreibersite veins and the occurrence of some comb plessite are evident in the structure. The iron meteorite Sikhote-Alin is a heavily deformed, coarse octahedrite containing 5.94% Ni, 0.38% Co, and 0.46% P. departmental bulletin paper